Deconstructing Collywood: A Conceptual Discourse on the Camerooness and Nigerianisation of Cameroon’s Video Film Industry - Endong Floribert Patrick C. (International Journal of Media and Communication Research (IJMCR), 2022)
Since its inception in 2008, the Cameroonian video film industry (codenamed Collywood) has attracted mitigated criticism from both Cameroonian and foreign commentators. This criticism has partly bordered on the “camerooness” versus the “foreignness” of Collywood. While a number of critics are of the persuasion that the above-mentioned cinematic movement is not only nigerianised but one of the multiple vectors of the nigerianisation of the Cameroonian cinema industry, others instead think that, by copying the Nollywood model, Cameroonian cineastes may boost their film production and ultimately inundate the local market with movies that speak to local cultures and reflect the quotidian experiences of Cameroonians. Using three methods of data collection (namely secondary sources, unofficial interviews with cineastes and critical observations), this paper revisits the above-mentioned debate and some of the thorny issues that have stemmed from the emergence, evolution, and enculturation of Collywood. The paper aims specifically at examining the camerooness versus the nigerianess of the Collywood movement. The paper attains four principal objectives: in the first place, it critically examines the creation and vision of Collywood, as well as its representativeness of Cameroon’s socio-cultural dynamics. In the second place, it explores the extent to which Collywood may be said to capture the aspirations of Cameroonian cineastes. Thirdly, the paper critically examines the extent to which Collywood is a nigerianised movement and an agent of the Nollywoodisation of the Cameroonian film industry. In the last place, it shows how the idea of copying the Nollywood model may enable or has been enabling the success of Collywood. Among other findings, the paper argues that Collywood is majorly a Nollywoodised Anglophone movement. Its Nigerianisation is just an inevitable outcome of the globalization/transnationalisation of the Nollywood model.